High yield debt : an insider's guide to the marketplace - Bagaria, Rajay, 1977- (Wiley, 2016)
"Examine the high yield market for a clear understanding of this evolving asset class High Yield Debt is the one-stop resource for wealth advisors seeking an in-depth understanding of this misunderstood asset class. The high yield market provides a diverse opportunity set, including fixed and floating rate debt, high and low quality debt issues and both short- and long-term duration; but many fail to understand that not all high yield exposure is the same, and that different market segments and strategies work best at different points in the economic cycle. This guide addresses the confusion surrounding high yield debt. You'll find the information you need to decide whether or not to buy in to a high yield fund, and how to evaluate the opportunities and risks without getting lost in the jargon. The U.S. corporate high yield market is worth $2.4 trillion--more than the stock markets of most developed countries. Market growth has increased the number of funds with high yield exposure, as well as the types of debt products available for investment. This book breaks it down into concrete terms, providing the answers advisors need to effectively evaluate the opportunities on offer. Understand the high yield asset class Learn the debt structures, performance and defaults Evaluate risk and investment opportunities Penetrate the jargon to make sense of high yield investment Over 300 publicly traded funds provide exposure to U.S. high yield, but despite it's size and ubiquity, understanding of the asset class as a whole remains somewhat of a rarity--even among participants. A lack of transparency is partially to blame, but the market's evolution over the past fifteen years is the larger issue. High Yield Debt explains the modern high yield market in real terms, providing a much-needed resource for the savvy investor"--